Extent of illicit cigarette market from single stick sales in Ghana: findings from a cross-sectional survey. Issue 3 (22nd March 2023) - Singh, Arti; Ross, Hana; Dobbie, Fiona; Gallagher, Allen; Kinnunen, Tarja; Logo, Divine Darlington; Boateng, Olivia A; Gilmore, Anna; Bauld, Linda; Owusu-Dabo, Ellis
Abstract : Objective: This study aims to measure the extent of illicit cigarette consumption from single stick sales, to determine the nature and types of illicit cigarettes present in Ghana, and to identify the factors associated with illicit cigarette consumption in Ghana. Design: A cross-sectional study using empty cigarette packs generated by 1 day's single stick cigarette sales collected from cigarette vendors. Setting: Five large cities (Accra, Kumasi, Takoradi, Tamale and Bolgatanga) and three border towns (Aflao, Paga/Hamele and Elubo) in the northern, middle and coastal belt of Ghana. Procedure and participants: Ten areas were randomly selected in each city/town, and all shops selling cigarettes within 1 km of the central point were surveyed. Outcome measures: (1) Estimates of the share of illicit cigarette packs in the total cigarette sales from vendors selling single stick cigarettes in Ghana; (2) nature and types of illicit cigarette packs; (3) factors associated with illicit cigarette sales in Ghana. Results: Of a total of 4461 packs, about 20% (95% CI 18.3 to 20.7) were found to be illicit. Aflao (Ghana-Togo border) and Tamale (Ghana-Burkina Faso border) had the highest percentage of illicit cigarette sales at 99% and 46%, respectively (p<0.001). Over half of the illicit packs originated from Togo (51%), followed by Nigeria (15%) and then Cote d'Ivoire (10%). Adjusted and unadjusted logistic regression models indicated that convenience stores, border towns, pack price and the northern zone had higher odds of illicit cigarette sales. Conclusion: To effectively tackle illicit cigarettes, market surveillance and strengthening supply chain control are required, particularly at the border towns and the northern region of the country.